Determining Factors Influencing The Successful Embryo Transfer and Pregnancy during The Frozen Cycle of In Vitro Fertilization: A Retrospective Cohort Study - Chanakarn Suebthawinkul; Pranee Numchaisrika; Akarawin Chaengsawang; Vijakhana Pilaisangsuree; Sadanan Summat; Wisan Sereepapong (International Journal of Fertility and Sterility, 2024)
Background: Frozen embryo transfer (FET) has been increasingly used due to advancements in cryopreservation techniquesand the safety advantages. This study aims to determine various factors influencing the successful FET.Materials and Methods: Retrospective cohort analysis included 1112 women who underwent programmed FET betweenJanuary 2012 and October 2022, at King Chulalongkorn Memorial Hospital, Thailand. Patient characteristics, embryocharacteristics, endometrial preparation protocol, endometrial characteristics (thickness, pattern), embryo transferprocedure (tip and flow during transfer, embryo placement location, the difficulty of the procedure, presence of bloodand mucous at catheter), and operator factor were analyzed. Multiple logistic regression analysis was used to assess therelationship between collected variables and successful embryo transfer which is defined by clinical pregnancy.Results: The overall clinical pregnancy rate was 34.2%. Women aged 35-40 years and >40 years were less likelyto have a clinical pregnancy compared to those aged <35 years [adjusted odds ratio (aOR): 0.523; 95% confidenceintervals (CI): 0.360-0.757, P<0.001 and aOR: 0.260; 95% CI: 0.152-0.434, P<0.001, respectively]. Obese womenwith body mass index (BMI) ≥25 kg/m2 were significantly associated with decreased clinical pregnancy (aOR: 0.632;95% CI: 0.403-0.978, P=0.042) compared to those with normal BMI. Day-3 and day-4 embryo transfer showed a significantdecrease in clinical pregnancy compared to blastocyst transfer (aOR: 0.294; 95% CI: 0.173-0.485, P<0.001and aOR: 0.497; 95% CI: 0.265-0.900, P=0.024). Double embryo transfer (DET) was 1.78 times more likely to have aclinical pregnancy than women with single embryo transfer (SET) (aOR: 1.779; 95% CI: 1.293-2.458, P<0.001). Thecycles with endometrial thickness <8 mm were associated with a decrease in clinical pregnancy compared with thosewith a thickness ≥8 mm (aOR: 0.443; 95% CI: 0.225-0.823, P=0.013).Conclusion: Older age, obesity, non-blastocyst transfer, single embryo transfer, and endometrial thickness of <8 mmwere significantly associated with a decreased clinical pregnancy in programmed FET.